Proliferation, bcl-2 expression and angiogenesis in pituitary adenomas: relationship to tumour behaviour. - Turner, H; Nagy, Z; Gatter, K; Esiri, M; Wass, J; Harris, A (2000)
The prediction of pituitary tumour behaviour, in terms of response to treatment from which can be derived optimal management strategies, is a challenge that has been approached using several different means. Angiogenesis in other tumour types has been shown to be correlated with poor response to treatment and tumour recurrence. The aim of this paper is to assess the role of measurements of cell proliferation and angiogenesis in predicting pituitary tumour behaviour. The proliferative capacity of the tumour was assessed using the Ki-67 labelling index (LI) while bcl-2 expression was used to assess anti-apoptotic pathways. The microvessel density (MVD) was assessed using antibodies to CD31 and factor VIII-related antigen, and with biotinylated ulex europaeus agglutinin I. There was no difference between Ki-67 LI and MVD of functionless tumours that recurred and those that did not, but bcl-2 expression was significantly lower in tumours that subsequently regrew. Macroprolactinomas had significantly higher LI than microprolactinomas and than all other tumours. Cell proliferation and angiogenesis were not related, showing that both processes are under different control mechanisms in pituitary tumours. In contrast there was a positive relationship between markers of angiogenesis and bcl-2 expression in prolactinomas, GH-secreting tumours and non-recurrent functionless tumours with higher levels of bcl-2 expression being found in the more vascular tumours. These findings may suggest that angiogenesis is related to the ability of tumour cells to survive rather than their proliferative activity.